APPLICATION OF HEMATITE SYNTHESIZED FROM IRON RUST WASTE AS A PIGMENT DYES FOR COTTON TEXTILE PRINTING - Asiyah Nurrahmajanti; Octianne Djamaludin; Wulan Safrihatini Atikah (Indonesian Journal of Chemistry and Environment, 2026)
Iron rust is an abundant waste material with potential to be utilized as an iron oxide pigment. While previous studies have focused on its synthesis, its application in textile printing remains limited. This study evaluates the performance of hematite (Fe₂O₃) derived from iron rust waste as a pigment for cotton fabric printing. The pigment was incorporated into a conventional printing formulation and applied onto cotton fabric. Color strength (K/S), CIELAB properties, and fastness to washing and rubbing were evaluated with five replicates to ensure data reliability. The results show a slight increase in K/S from 1.13 ± 0.09 to 1.22 ± 0.10 with increasing synthesis concentration, although the difference remains moderate. The printed fabrics exhibited consistent reddish-yellow hues and low variability in colorimetric values, indicating good reproducibility. Washing fastness was acceptable (grade 3 for color change; 4–5 for staining), while rubbing fastness ranged from 2–4. These findings demonstrate that rust-derived hematite is applicable as a pigment in textile printing. However, performance is influenced by pigment–binder interaction, indicating the need for further optimization to improve color strength and durability.